La velocidad lectora y su relación con la comprensión lectora en los estudiantes del 2do grado de primaria de la I.E José Carlos Mariátegui - Mocarro Encarnación, Jacqueline (2016)
Reading is an essential part of literacy skills, and in turn to read, it is the process that performs the understanding of written language, and allows the establishment of an interaction between reader and text. From the methodological point of view, the problems of reading speed would be cond itional comprehension d ifficulties. The overall objective of this research was to determine the relationship between reading speed and reading comprehension in students of the 2nd grade education II.EE. "Jose Carlos Mareategui" Sector Rupacucha- Rioja Reading comprehension is based on the theories: Outline, understanding as an interactiva, transactional and process understanding and reading as a skill set or knowledge transfer. The research design was a correlational substantive, descriptiva cross-sectional research. The sample consisted of 57 students divided into two. sections "C" and "8" of the 2nd degree. The experiment was carried out for a month, with the application of the test ofreading speed and reading comprehension in students individually, achieving accepting our research hypothesis, meaning that there is a significant positiva relationship . between reading speed and reading · comprehension Students in 2nd grade education II.EE. "Jose Carlos Mareategui" Rupacucha Sector - Rioja with a Pearson. correlation coefficient (Ys = 0,715 }.